2010
DOI: 10.1016/j.jconrel.2010.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Insights in cellular uptake mechanisms of pDNA–polycationic amphiphilic cyclodextrin nanoparticles (CDplexes)

Abstract: have equally contributed to the reported work. Abstr actIt is generally recognized that the major obstacle to efficient gene delivery is cellular internalization and endosomal escape of the DNA. Recently, we have developed a modular strategy for the preparation of well-defined polycationic amphiphilic cyclodextrins (paCDs) capable of complexing and compacting DNA into homogeneous nanoparticles (<70 nm).Since paCDs resemble both cationic polymers and cationic lipids, it is conceivable that the corresponding pDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 61 publications
1
74
1
Order By: Relevance
“…Vero African green monkey kidney epithelial cells indicated that CME and CvME are the major routes of uptake for this particular CD (Diaz-Moscoso et al 2010). This is in contrast to the results obtained in the current study and may be explained by structural variations between the CDs and cell type dependent effects.…”
Section: Discussioncontrasting
confidence: 99%
“…Vero African green monkey kidney epithelial cells indicated that CME and CvME are the major routes of uptake for this particular CD (Diaz-Moscoso et al 2010). This is in contrast to the results obtained in the current study and may be explained by structural variations between the CDs and cell type dependent effects.…”
Section: Discussioncontrasting
confidence: 99%
“…However, these authors did not measure cytosolic delivery, and the pH of 5 required for dissociation is unlikely to be of value for RNA delivery. Polycationic, amphiphilic cyclodextran has been used for DNA delivery [73], although this work focused on epithelial cell lines rather than DC. Dierendonck et alreviewed the work employing hydrogen bonded capsules assembled using poly(methacrylic acid) and degradable dextran sulfate/poly-l-arginine; reductionsensitive linkages were incorporated into the polymers, without introducing polycations [74].…”
Section: Cationic Lipid-based Delivery To DCmentioning
confidence: 99%
“…[78] This work demonstrated a macropinocytosis-mediated uptake mechanism for the dendrimer-miRNA complexes, with substantially improved efficiency in comparison to the original PAMAM formulations reported. [79] Similarly, cyclodextrins undergo unspecific (clathrin independent) uptake [80] but also serve to improve water-solubility and biodistribution of the cargo due to their cyclic oligosaccharide nature. [81] In the case of CPPs, uptake may occur either through transitory micelle formation, endocytosis in its four variants, or direct penetration driven by penetratin or TAT (GRKKR-RQRRR) domains, [82] which explains their documented high transfection efficiencies.…”
Section: Nonviral Vectorsmentioning
confidence: 99%